2016
DOI: 10.1038/srep30870
|View full text |Cite
|
Sign up to set email alerts
|

ge-CRISPR - An integrated pipeline for the prediction and analysis of sgRNAs genome editing efficiency for CRISPR/Cas system

Abstract: Genome editing by sgRNA a component of CRISPR/Cas system emerged as a preferred technology for genome editing in recent years. However, activity and stability of sgRNA in genome targeting is greatly influenced by its sequence features. In this endeavor, a few prediction tools have been developed to design effective sgRNAs but these methods have their own limitations. Therefore, we have developed “ge-CRISPR” using high throughput data for the prediction and analysis of sgRNAs genome editing efficiency. Predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 55 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…Whether the activity of these sgRNAs could be predicted by the publicly available sgRNA design tools was then determined. All 87 sgRNAs were scored using sgRNA Scorer 2.0 (29) and ge-CRISPR (30), which were trained from eukaryotic data sets. The predicted score then was compared with the observed activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whether the activity of these sgRNAs could be predicted by the publicly available sgRNA design tools was then determined. All 87 sgRNAs were scored using sgRNA Scorer 2.0 (29) and ge-CRISPR (30), which were trained from eukaryotic data sets. The predicted score then was compared with the observed activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon inspecting the structure of the SpCas9 RNP poised to cleave a DNA target (Jiang et 340 al., 2016), we concluded that sequences adjacent to and upstream of the PAM sequence (5'-NGG-3'), which have been reported to bias SpCas9 activity in vivo (Doench et al, 2014;Wu et al, 2014;Xu et al, 2015;Moreno-Mateos et al, 2015;Horlbeck et al, 2016;Liu et al, 2016;Kaur et al, 2016;Gandhi et al, 2017), likely influence SpCas9 recognition by stabilizing the conformation of the DNA target for cleavage. Therefore, we accounted for biases in SpCas9 345 recognition by choosing gRNAs sequences that conformed, as much as possible, to the motif 5'-HNNGRSGGH-3', in which the PAM is underlined, N stands for any base, R stands for purine, S stands for G or C, and H stands for any base except G. This motif was first used to search for suitable targets (Peng and Tarleton, 2015) in cDNA sequences.…”
Section: Design and Preparation Of Grnasmentioning
confidence: 87%
“…Genus Brachybacterium are widely distributed in various environments. From marine environments, B. aquaticum has been successfully isolated from seawater (Kaur et al, 2016). Zhang et al, (2007) reported that Brachybacterium zhongshanense sp.…”
Section: Molecular Identification Of Bacterial Strain Sj04mentioning
confidence: 99%